Improvement of High School Students' Speaking Arabic Skills Through Video Dubbing - Al-Husain Al-Hammadi; Abdul Azis; Yusri Rahman (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2022)
This study is aimed to know the effect of video dubbing on Arabic students’ and English-speaking fluency at the second grade of SMAN 1 Gunungsari in academic year 2020/2021. The approach of this research is quantitative research and the type of the research is quasi experimental research using one group pre-test and post-test design. The methods of data collection are carried out by means of documentation and speaking test. The result of this study shows that the implementation of video dubbing on student’s Arabic and English-speaking skill has a significant effect and makes the students spoke fluently. It was proved by the mean score in the post-test was higher than mean score in the pre-test and result of t-test shows that t-test 4.205 is higher than t-table 2.024. Besides, the researcher found that the students were able to speak confidently and they had many vocabularies which could not be found in others previous research. It can be concluded that the implementation of video dubbing on students’ Arabic and English-speaking skill has a good effect and successfully made the students spoke fluently.